Kepastian Hukum Penyelesaian Sengketa Persaingan Usaha dengan Terciptanya Pengadilan Persaingan Usaha - Junaidi, Junaidi (Zaaken: Journal of Civil and Business Law, 2025)
In the context of trade, rivalry or business competition is an inevitable phenomenon in a country's economic ecosystem. Competition law is an important tool in a market economy, because through this tool the government seeks to protect fair competition between economic actors in the market. The Business Competition Supervisory Commission (KPPU) was established based on Law Number 5 of 1999. This research uses normative legal research methods. Normative legal research method is library research conducted by examining library documents or secondary data. By applying the deductive method, which is a way of thinking that draws conclusions based on general matters that have been proven correct, and these conclusions are applied to special matters. The issuance of Law Number 11 of 2020 concerning Job Creation, changes in provisions related to the points of change in articles 44, 45, 46, 47, 48 and the abolition of Article 49. These changes also create legal uncertainty regarding ongoing adjustments, especially regarding the provisions of administrative sanctions and changes to the main criminal sanctions. The Business Competition Supervisory Commission (KPPU) in investigating reports of unfair business competition relies on indirect evidence. The reason is that the Business Competition Supervisory Commission (KPPU) does not have the authority to conduct investigations, searches, and seizures in investigating business competition cases. This causes the decision to not be able to reflect and realise legal certainty. For this reason, it is necessary to have a judicial body that specifically handles business competition issues to enforce the law and ensure legal certainty of business competition.